Pengembangan Bahan Ajar Bahasa Arab Berbasis Kurikulum Merdeka Belajar - Bukhori, Evi Muzaiyidah; Sulton, Ahmad (Jurusan Pendidikan Bahasa Arab IAIN Ponorogo, 2024)
This study was conducted to develop an Arabic e-module based on the Merdeka Belajar curriculum. The purpose of this study was to describe the validation of the Arabic e-module and the effectiveness of using the developed e-module. This study is an R&D study with the ADDIE development model. The evaluation instrument used tests and questionnaires and was analyzed using the T-Test. The results of the study are in the form of an Arabic e-module developed through a flipbook application, which includes features such as sound, images, animation, video, and more, that attract interest in learning and make it easier for students to understand Arabic material. Based on the results of the validity of media experts (92% very interesting), material experts (94% very interesting), and language experts (87.3% very interesting). The results of the limited trial between the control and experimental groups, analyzed with the T-test through the Independent Samples T-test on IMB SPSS 25.0, showed that the value of sig. (2-tailed) was 0.001, which is greater than 0.05. This means that Ha is accepted and H0 is rejected. The conclusion is that there is a significant difference between the Post-test learning outcomes of the control and experimental groups. Abstrak Penelitian ini dilakukan untuk mengembangkan e-modul Bahasa Arab berbasis kurikulum Merdeka Belajar. Tujuan penelitian ini untuk mendeskripsikan validasi e-modul Bahasa Arab dan efektifitas penggunaan e-modul yang dikembangkan. Penelitian ini merupakan penelitian R&D dengan model pengembangan ADDIE. Instrumen evaluasi menggunakan tes dan angket dan dianalisis dengan T-Test. Hasil penelitian berupa e-modul Bahasa Arab yang dikembangkan melalui aplikasi flipbook, di dalamnya terdapat fitur suara, gambar, animasi, video dan sebagainya menarik minat belajar serta memudahkan mahasiswa memahami materi Bahasa Arab. Berdasarkan hasil validitas ahli media sebesar 92% (sangat menarik), ahli materi sebesar 94% (sangat menarik), dan ahli bahasa sebesar 87,3% dengan (sangat menarik). Hasil uji coba terbatas antara kelompok kontrol dan eksperimen dengan uji T-test melalui Independent Samples T-test) pada IMB SPSS 25.0 menunjukkan bahwa nilai sig. (2-tailed) sebesar 0,001>0,05. Artinya Ha diterima dan H0 ditolak. Kesimpulannya bahwa terdapat perbedaan yang signifikan antara hasil belajar Post-test kelompok kontrol dan eksperimen.